Megalithic and non-megalithic monuments in the Kelabit Highlands of Sarawak - Nicholas Gani, (Ikatan Ahli Arkeologi Malaysia, Universiti Kebangsaan Malaysia, 2022)
The megalithic and non-megalithic monuments of the Kelabit Highlands gained prominence in archaeological circles and in public eyes through the pioneering research conducted by Tom Harrisson from the late 1940s to the 1970s. From the mid-1970s to 2000, however, there was a lack of new archaeological research on the monuments of the Kelabit Highlands. This changed beginning in the 2000s with new interests in the monuments of the Kelabit Highlands in terms of their preservation and conservation (Cluny and Chai 2007; Hitchner 2009), as well as in archaeological research (Barker et al. 2008; Barker et al. 2009; Lloyd-Smith et al. 2010; Lloyd-Smith 2012; Lloyd-Smith et al. 2013; Lloyd-Smith et al. 2017). With new findings coming to the fore in recent years, this paper reviews the present state of knowledge on the megalithic and non-megalithic monuments in the Kelabit Highlands of Sarawak. This review is based on the study of existing literature and archival research, as well as archaeological excavations and surveys, and ethnographic research conducted in the field by the author. First, this article discusses previous archaeological research conducted on the monuments. Following that, this article discusses the chronology of the monument building tradition in the Kelabit Highlands and the typology of monuments. Next, this article focuses on the social contexts of monument building, as well as the cultural significance of monuments to the Kelabit people. By employing both archaeological and ethnographic perspectives, this article contributes a more holistic and nuanced understanding of a monument building tradition in the Kelabit Highlands that began more than 2,000 years ago and continued until around the middle of the 20th century.